Self-protective biases in group categorization threat cues shape the psychological boundary between "Us" and "Them".[article]. - Miller, Saul L.
Across 6 studies, factors signaling potential vulnerability to harm produced a bias toward outgroup categorization-a tendency to categorize unfamiliar others as members of an outgroup rather than as members of one's ingroup. Studies 1 through 4 demonstrated that White participants were more likely to categorize target as Black (as opposed to White) when those targets displayed cues heuristically associated with threat(masculinity, movement toward the perceiver, and facial expression of anger). In study 5, White participants who felt chronically vulnerable to interpersonal threats categorized threatening(masculine) targets as outgroup members. Together, findings indicate that ecologically relevant threat cues within both the target anf the perceiver interact to bias the way the people initially parse the social world into ingroup vs. outgroup. Findings support a threat-based framework for intergroup psychology. -- (from the author)